If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(4x + 7) = 113 Reorder the terms: 3x + 2(7 + 4x) = 113 3x + (7 * 2 + 4x * 2) = 113 3x + (14 + 8x) = 113 Reorder the terms: 14 + 3x + 8x = 113 Combine like terms: 3x + 8x = 11x 14 + 11x = 113 Solving 14 + 11x = 113 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 11x = 113 + -14 Combine like terms: 14 + -14 = 0 0 + 11x = 113 + -14 11x = 113 + -14 Combine like terms: 113 + -14 = 99 11x = 99 Divide each side by '11'. x = 9 Simplifying x = 9
| 17x^2-17=0 | | 21+6x=23+7x | | -3w+2=14 | | 25000x-5y=0 | | X+1.23=65.6 | | 15y-1=103 | | 9x-38=4x+23 | | 11-(x-2)=3 | | 4x+6=9x+1 | | 3x+3(5x-15)=63 | | 8+c=0 | | 8=c-12 | | x^2-14x+40=40 | | -0.23076923p=-2 | | -4(t-4)+9t=7t-6 | | (x-10)(x-4)=40 | | -3(1.2)(1.2)= | | 7y+5=9y | | 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 |